Technical or not? Investigating the self-image of girls aged 9 to 12 when participating in primary technology education - Sultan, Ulrika Napoleon; Axell, Cecilia; Hallström, Jonas (Design and Technology Education: An International Journal, 2020)
Variance in interest and engagement by gender is a complex and long-standing research agenda in the field of technology education. Studies report that girls are more reluctant to participate in technology education, less interested in the subject and more negative towards technology than boys. It is argued that specific attitudes and roles hinder girls from engaging in technology education because technology is presented as a predominantly male domain, which fuels ideas about what technological agency is as well as whose interest in technology and what kind of technology are regarded as legitimate. There is, however, the potential to improve female engagement if we can gain knowledge about what girls do during lessons and how they think about themselves when learning technology. Therefore, the aim of this study is to examine the self-image of girls aged 9 to 12 when participating in primary technology education, by using Harding’s (1986) three gender levels: the symbolic, the structural and the individual. The methods used for this study were participant observations during technology classes followed by a focus group interview. From the perspective of Harding’s three levels of gender, the analysis of the observations and the focus group interview reveals that girls confirm the prevailing male norms and conceptions that are linked to what technology is and what it means “to be technical”, despite the fact that the teacher introduces gender-neutral activities. However, there is an ambiguity in our findings because the girls also resist the self-image of not being technical, especially when they work together and have ownership of their work with and learning about technology.